Pengaruh Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan Opal Coffee Medan - Purba, Yessica Sardina; Hendy, Hendy; Kezia, Grace (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of discipline and environment on employees’ performance of Opal Coffee Medan. This type of research is explanatory research. The Population in this study were all employees of Opal Coffee Medan, totaling 57 employees. The sampling technique is to use a saturated sample where the entire population will be used as the research sample. In the study which will be distributed with questionaires measured by a Likert scale. The data analysis used multiple linear regression analysis and the coefficient of determination as well as simultaneous test and partial test. The results showed that discipline and environmental partially or simultaneously have a positive and significant effect on employee achievement of Opal Coffee Medan. The result of the coefficient of determination test showed that the value of R Square Showed that the influence of discipline and environment on work performance was 57.1% and the remaining 42.9% was influenced by other factors originating from outside this research model such as given incentive and internal communication. Based on the results of this study, the implications for management are to further improve discipline and quality of environment. Keywords: Employees’Performance, Work Discipline, Work Environment,